a)6x(5x-24)-4(3-2x)^2
б)2y(11y-9)+0,5(4y-3)(4y+3)
в)(a-3b) (a+3b)+(2a-3b)^2-4a(b-a)
г) (x+6y)^2-(6y+5x) (6y-5x)+x(12y-6x)

a)6x(5x-24)-4(3-2x)^2
б)2y(11y-9)+0,5(4y-3)(4y+3)
в)(a-3b) (a+3b)+(2a-3b)^2-4a(b-a)
г) (x+6y)^2-(6y+5x) (6y-5x)+x(12y-6x)

15-03-2019 18:21 Просмотры: 0
Ответы (1)
Айрик Любезный
+5
2019-03-15 22:26:59

а) 6х(5х-24)-4(3-2х)^2=30x-144-4(9-12x+4x^2)=30x^2-144-(36-48x+16x^2)=30x^2-144-36+48x-16x^2=14x^2+48x-180=2(7x^2+24x-90) b) 2y(11y-9)+0,5(4y-3)(4y+3)=22y^2-18y+0,5(16y^2-9)=22y^2-18y+8y^2-4,5=30y^2-18y-4,5 c) (a-3b)(a+3b)+(2a-3b)^2-4a(b-a)=a^2-9b^2+4a^2-12ab+9b^2-4ab+4a^2=9a^2-16ab=3(3a^2-8ab) d) (x+6y)^2-(6y+5x)(6y-5x)+x(12y-6x)=x^2+12xy+36y^2-(36y^2-25x^2)+12xy-6x^2=20x^2+24xy=4x(5x+6y)